Accessory lobe of liver: intra-operative incidental finding: a rare case report - Wani, Ab Hamid; Singh, Gurbir; Singh, Abhimanyu; Kumar, Rajat (International Journal of Research in Medical Sciences, 2025)
An accessory lobe of liver is a rare congenital anomaly, but is usually an incidental finding during abdominal surgeries. The condition is usually asymptomatic. Here, we report a case where the accessory liver lobe was an incidental finding during laparoscopic Cholecystectomy. An accessory liver lobe resection should be done to prevent complications and malignant transformation.